The Constitution, the law, and freedom of expression, 1787-1987 - Stewart, James Brewer; Burger, Warren E., 1907-1995 (Southern Illinois University Press, 1987)
Contributions to the 1st Wallace Conference on "The Constitution, Freedom of Expression, and the Liberal Arts," held in Sept. 1986 at Macalester College ; sponsored by the college.
Contributions to the 1st Wallace Conference on "the Constitution, Freedom of Expression, and the Liberal Arts," held in Sept. 1986 at Macalester College; sponsored by the college.
Keywords: Freedom of speech -- United States -- History -- Congresses.; Freedom of the press -- United States -- History -- Congresses.; Liberté d'expression -- États-Unis -- Histoire -- Congrès.; Liberté de la presse -- États-Unis -- Histoire -- Congrès.; POLITICAL SCIENCE -- Government -- Judicial Branch.; LAW -- Legal Services.; LAW -- Civil Procedure.; LAW -- Constitutional.; LAW -- Public.; Freedom of the press -- United States -- History.; Freedom of speech -- United States -- History.; Freedom of speech; Freedom of the press; United States; The Chris Fritz Comparative and Historical Legal Perspectives Collection (CHLP); Conference papers and proceedings; History; proceedings (reports); Conference papers and proceedings.; Actes de congrès.